A NEW MODEL FOR THE FORMATION OF DOLOMITE IN THE TRIASSIC DOLOMITES, NORTHERN ITALY. (January 2015) - Blendinger, W.; Lohmeier, S.; Bertini, A.; Meißner, E.; Sattler, C.-D.
<x xml:space="preserve">Abstract</x> The Pale di San Martino and Pale di San Lucano (referred to together as the "Pale") are remnants of an originally more extensive carbonate platform in the Dolomite Mountains of northern Italy. The platforms are composed of Middle Triassic dolomites and limestones up to 1.6km thick. Limestones comprise 2–3% of the platform carbonates and are restricted to narrow corridors (tens to a few hundred metres wide, hundreds of metres long and high) within the dolomite. The mainly sucrosic dolomites of the Pale are interpreted as the result of recrystallization of a depositional, nearly stoichiometric Mg calcite under burial temperatures of ca. 40–70°C. The principal arguments are: The quantitative composition indicates that all platform carbonates are composed mainly of micritic crusts (45%; boundstone fabric prevails) and early cement (35%; microcrystalline, fibrous). The platform carbonates were probably mainly bacterial precipitates and tight at the sediment‐water interface (porosities <5%, permeabilities in the micro‐Darcy range). The limestone‐dolomite transitions (centimetres to decimetres wide) lack dolomite gradients. The lack of evidence for flowing fluids causing dolomitization suggests stagnant pore waters. The δ13C of average dolomite is 1.3‰ heavier than that of coeval limestone (666 analyses). The difference corresponds to a primary difference of 50mol% MgCO3 and is interpreted as the result of fractionation. It suggests a dolomite precursor of very high Mg calcite, whereas present‐day limestone of the Pale was probably deposited as a basically Mg‐free polymorph (aragonite and/or calcite). The dolomite δ18O (+1 to −11‰ VPDB) values show a scatter over the platform thickness and preserve randomly distributed values around 0‰. The scatter is probably due to selective re‐setting of δ18O near pore spaces and is mainly a sampling effect. The observation that 87Sr/86Sr ratios (77 analyses) of limestone and dolomite are either slightly higher or lower than Middle Triassic seawater, but almost never "normal marine", suggests that the platform carbonates of the Pale were deposited from seawater contaminated with artesian freshwater. The limestone corridors are probably caused by artesian springs of somewhat higher than ambient depositional temperature, with low Mg calcite and/or aragonite deposited in or near fracture zones. The volumetrically subordinate cycle‐cap dolomite is possibly a primary precipitate.